Perancangan Sistem Ujian Online Berbasis Web di Sekolah Menengah Kejuruan (Smk) Maraqitta’limat Mamben - Sadali, Muhamad; Sarkasih, Suryadi (Fakultas Teknik Universitas Hamzanwadi, 2018)
Maraqitta'limat Vocational High School (SMK MT) Mamben is one of the institutions engaged in education. This school has a goal that is to build the quality of the nation's children to be more advanced in the world of education in accordance with the capabilities and technological advances that are developing at this time. In the world of education, evaluation of learning outcomes is done for students to find out the level of ability or success during the educational process. This test or test is conducted periodically or within a certain period of time during the education period. In educational institutions, the exam activities are carried out in two ways, both in writing and in practice, including the Maraqitta'limat Mamben Vocational High School (MT Mamben Vocational School) holding the semester examination process. On the implementation of the semester exam a thought arises, how to make the process of conducting an online exam more easy and efficient, beneficial for teachers and students by utilizing the advancement of computer technology by maximizing the availability of infrastructure available in the Maraqitta'limat Mamben Vocational School which already has a computer laboratory adequate. Web-Based Online Examination System using PHP, MYSQL and Macromedia Dreamweaver 8 is expected to help the performance of School Operators / admin who handle Semester Exams. And it is expected to facilitate the recording of the test score report.DOI : 10.29408/jit.v1i1.934